A modified peridynamic method to model the fracture behaviour of nanocomposites. (15th April 2021) - Ma, Dayou; Verleysen, Patricia; Chandran, Sarath; Giglio, Marco; Manes, Andrea
Highlights: Peridynamic method is used to replicate the fracture behaviours of nanocomposites. The presence of nanoparticles, HBP, is simulated at macroscale by constrained nodes. Rapid-slow-rapid increasing fracture toughness is obtained as weight fraction rises obtained. Effect of HBP particles' distribution on the fracture behaviour is investigated. Abstract: In the present work, a numerical investigation based on a modified peridynamic method of fracture properties of epoxy resin reinforced by nanoparticles, more specifically hyperbranched polyester (HBP), was conducted. Due to the specific features of HBP, certain material nodes in the numerical model were constrained to accurately replicate the effect of HBP in pure epoxy resin, and a Monte Carlo method was used to simulate the random distribution of HBP. The numerical model was validated by fracture tests with single-edge-notched bending (SENB) samples. Moreover, the effect of the HBP weight fraction on the fracture properties was analysed. With increaseing HBP weight fraction, a three-stage increase of mode-I fracture toughness in a rapid-slow-rapid manner was obtained. Overall, the proposed modified peridynamic method provided a macroscale analysis of the fracture behaviour of nanocomposites reinforced by HBP in a simulation framework.